Printed information, education, and communication materials utilization and associated factors among health care providers in central Ethiopia - Geleta, Tinsae Abeya; Deriba, Berhanu Senbeta; Dirirsa, Dejene Edosa; Beyane, Rebik Shukure; Nigussie, Tadesse; Legesse, Elsabeth; Jemal, Kemal; Gemeda, Dirreba; Debela, Sisay Abebe; Workneh, Abiot Aschale (Frontiers in Communication, 2022)
Abstract Introduction: Information, education, and communication (IEC) is a combination of strategies, approaches, and methods that enable individuals, families, groups, organizations, and communities to play an active role in achieving, protecting, and sustaining their health. Healthcare providers are responsible for providing health education to the community through the use of different types of health learning materials. Printed IEC materials were damp and wasted without being used in the study area. Therefore, this study aimed to assess the utilization of printed IEC materials, and associated factors among health care providers in the north Shoa zone, Oromia regional state, Ethiopia Methods: A facility-based cross-sectional study was conducted in the North Shoa zone, Oromia region, Ethiopia. The simple random sampling technique was used to select 297 study participants. Data were collected using a self-administered questionnaire and entered into the Epi-data manager version 4.4.1 and exported to SPSS version 23 for data analysis. Bivariate and multivariate logistic regression analysis was performed to see the association between dependent and independent variables. Result: A total of 281 health care providers participated in the study, with a response rate of 95%. Eighty-four percent of the study participants were known about printed IEC material. About 235(83.6%) respondents ever used printed IEC material and 171(60.9%) study participants used printed IEC material last month. About 259(92.2%) participants had the intention of using IEC material in the future. Age, sex, marital status, having enough time to provide health education, and perceiving the importance of the IEC to provide basic concepts were significantly associated with the use of IEC material. Conclusions: Generally, the results of this study indicated that the utilization of printed IEC materials was high. To increase utilization of printed IEC material, coordinated efforts were required from the federal government, regional government, non-government organizations, the zonal health bureau, and health facilities. Keywords: IEC, Health Information, Health Communication